2012
DOI: 10.1111/j.1467-6494.2012.00764.x
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Integration of Agency and Communion: A Study of Influential Moral Figures

Abstract: The purpose of this research is to (a) identify which of recent history's influential figures did and which did not personify moral excellence, and (b) to examine the motives that drove these individuals along such divergent paths. In Study 1, 102 social scientists evaluated the moral qualities of influential figures from Time Magazine's lists. In Study 2, we selected the 15 top ranking of these figures to comprise a moral exemplar group and the bottom 15 to comprise a comparison group of similarly influential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(32 citation statements)
references
References 16 publications
1
31
0
Order By: Relevance
“…Frimer and colleagues have shown that on moral character traits such virtuousness, principledness, and fairness, different judges agree in their assessments of influential cultural figures (Frimer, Walker, Lee, Riches, & Dunlop, 2012;Frimer, Biesanz, Walker & MacKinlay, 2013). It is unclear from these findings, however, whether informants would agree in their perceptions of a familiar, but not famous, person, with whom they have a great deal of first-hand experience, and about whom no cultural stereotypes exist.…”
Section: Evidence For Agreement On Moral Charactermentioning
confidence: 43%
“…Frimer and colleagues have shown that on moral character traits such virtuousness, principledness, and fairness, different judges agree in their assessments of influential cultural figures (Frimer, Walker, Lee, Riches, & Dunlop, 2012;Frimer, Biesanz, Walker & MacKinlay, 2013). It is unclear from these findings, however, whether informants would agree in their perceptions of a familiar, but not famous, person, with whom they have a great deal of first-hand experience, and about whom no cultural stereotypes exist.…”
Section: Evidence For Agreement On Moral Charactermentioning
confidence: 43%
“…After all, it is hard to think of a domain that affords the expression of communion any better than the domain of prosociality. In line with that, past theory has exclusively tied prosociality to communion but not to agency (with moral exemplars being an exception to that rule; Frimer & Oakes, 2013;Frimer, Walker, Dunlop, Lee, & Riches, 2011;Frimer, Walker, Riches, Lee, & Dunlop, 2012). Hence, expressiveness processes may leave little room for social motives processes.…”
Section: Big Two Personality and Prosociality: May Social Motives Matmentioning
confidence: 80%
“…In organizational research, it is often assumed that people with highly pronounced concern both for themselves and for others generate the most persistent contributions to others (Frimer et al 2012;Grant 2014;Bolino and Grant 2016). Grant (2014) suggests that organizational performance benefits most from people with a high emphasis on both types of motivation at the same time.…”
Section: Discussionmentioning
confidence: 99%